Pharmacoeconomics as an instrument of clinical pharmacology for optimization of pharmacotherapy (review) - O. V. Reshet'ko; K. A. Lutsevich (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Pharmacoeconomics is an essential component of health technology assessment and the appraisal of medicines for use by patients. As a comparatively young discipline, its methods continue to evolve. Pharmacoeconomic analysis encompass cost-minimization, cost-utility, cost-benefit, and cost-effectiveness studies, providing essential information critical for optimization of pharmacotherapy, optimal healthcare resource allocation and drug development success.